A proposed integration of the event and project management body of knowledge - van Antwerpen, Sumei (International Journal of Applied Sciences in Tourism and Events, 2023)
The concept of an established international body of knowledge implies being updated with a respected good standing. The EMBOK (event management body of knowledge) may have some limitations in need of an update to be clearly distinguished. EM (event management) need a special kind of management considering the scope of the event industry with unfortunate event failures. The comprehensive nature of any body of knowledge (BOK) study led to a pre-study with respect to a conceptual integrated exploratory methodology. This provided the freedom to move outside conservatism to relate ideas, notions, theories, impressions and abstractions to the problem. The purpose was therefore not to obtain a final account but to propose a well-defined hypothesis for further studies. The conceptual data less structured casual observation, and an overview of secondary sources and literature. The overall exploratory study indicates a need for the update of the EMBOK also by means of the PMBOK (project management body of knowledge) or a synthesised event-project management framework (E-PMBOK).